Nafamostat Mesylate Regulates Glycosylation to Alleviate Aristolochic Acid Induced Kidney Injury - Pei Xie; Huijun Liu; Xingli Huo; Junlong Chen; Yu Li; Yu Huang; Zongning Yin (Toxins)
Acute kidney injury (AKI) is a condition with a poor prognosis, exacerbated by the lack of effective therapeutic options and inadequately understood underlying mechanisms. Glycosylation, a post-translational modification of proteins, is essential for maintaining protein stability and function, and its dysregulation leads to protein misfolding and amyloid aggregation. Glycosylation dynamics are implicated in several pathologies, including inflammation, cancer, and AKI, highlighting the therapeutic potential of regulating glycosylation and preventing aggregation in AKI treatment. This study investigates the effect of nafamostat mesylate (NM) on protein glycosylation and amyloid aggregation in vivo. Using optical spectroscopy and other analytical techniques, we demonstrate that NM restores glycosylation levels and inhibits protein aggregation in aristolochic-acid-induced acute kidney injury. The mechanism likely involves enzymatic modulation that corrects hypoglycosylation and prevents amyloid aggregation, promoting proper protein folding and enhancing its stability. These findings suggest that NM may provide a novel therapeutic strategy for AKI and other glycosylation-related diseases, underscoring the potential for early intervention and treatment of these conditions.